Sustainable Biofuel Policies: Challenges and ethical considerations - Tsitrouli, Zinovia (Bioethica, 2021)
Over the last few decades, after the emergence of biofuels at commercial scale in the 1970s, several policies, at domestic or international level, have promoted these alternative fuels, citing mainly three supporting reasons: their potential to fight energy insecurity, ability to alleviate climate change through decreasing carbon dioxide in the atmosphere -compared to conventional fuels- and capacity to promote agriculture and rural development. But, ever since the beginning of their expansion, it became clear that biofuels are not as sustainable as originally thought. And since policies and national legislative frameworks are the main instruments guiding biofuels’ development, this article aims to focus on answering the question whether current biofuel policies are efficient in ensuring sustainability, while promoting biofuels. If this is found not to be the case, then an attempt will be made in order to examine the relative existing gaps, to discuss the potential conflicting interests and ultimately to proceed with recommending adequate alterations in legislations. Ethical dimensions will also be discussed, which could provide some insightful considerations for upcoming biofuel legislations.